Death Avoidance Attitude Among the Youth: Analysis in Nepalese Context - Karki, Tej Bahadur; D’Mello, Laveena (NPRC Journal of Multidisciplinary Research, 2025)
Background & Objective: The avoidance of death is a major psychological phenomenon that controls the approach and relation of human beings to the thought of death. The present paper studies the death attitude among Nepalese youths, focusing attention on gender differences as well as the sociocultural, religious, and socio-demographic factors causing death avoidance. Understanding these will help in the implications for the reduction of stigma about death and appropriate interventions.Methods: A cross-sectional descriptive and explanatory research design was adopted, where data were collected from 196 youths across Nepal using a random sampling technique. The Death Attitude Profile-Revised (DAP-R) was the standard instrument used for measuring attitudes toward death. The Chi-Square test, t-test and Levene's Test for Equality of Variances were conducted to test the differences in death avoidance attitudes between male and female participants.Key Findings: Results have indicated that while the mean score for the attitude of avoidance of death was a little higher for males than females, the difference was not significant. Both genders expressed a similar amount of discomfort when discussing the topic of death, suggesting that cultural factors are perhaps more influential than gender itself in shaping such attitudes. The findings have implications for context-specific research to understand the unique social and cultural dynamics at play.Conclusion & Recommendation: The study concludes that developing appropriate educational interventions promoting open discussions on death is important, which will facilitate a reduction in anxiety and stigma. Improvement in mental health resources is thus recommended to be provided for youths to work out their fears and attitudes toward mortality within the rich cultural context of Nepal.